Analysis of process intensification and performance assessment for fermentative continuous production of bioethanol in a multi-staged membrane-integrated bioreactor system. (1st September 2018) - Pal, Parimal; Kumar, Ramesh; Ghosh, Alak Kumar
Graphical abstract: Highlights: Analysis of a novel multi-staged membrane based process for bioethanol done. The process ensures high yield, productivity and purity at reduced cost. Solar driven DCMD shows high degree of process intensification on the new system. Achieved process intensification towards sustainability analysed in numerical terms. Abstract: The work analyses process intensification in production of fermentative biofuel (bioethanol) in a multi-staged membrane integrated bioreactor system from sugarcane juice (SCJ) using Saccharomyces cerevisiae (NCIM 3205). Membrane based clarification, sterilization and concentration of sugar cane juice could replace several energy-intensive and polluting steps of conventional production schemes. Integration of traditional bioreactor with membrane-based devices for downstream purification of bioethanol enabled the system for recycling of cells and residual sugars to the fermentation unit through largely fouling free cross flow microfiltration and nanofiltration membrane modules. The new process design is characterized by high yield (0.48 g/g), productivity (14.6 g/L/h) and concentration capability (97.6 g/L) using concentrated SCJ of 22 wt% under high cell density in a flexible, compact, eco-friendly and modular plant. The final membrane distillation stage concentrated ∼98% pure ethanol in a solar-driven direct contact membrane distillation configuration using PTFE/PET hydrophobic membrane with enhanced flux with vis-à-vis the existing processes. A rectangular flat sheet cross flow membrane module in counter-current flow mode of hot and cold streams was employed. The membrane-based system achieves quite high levels of process intensification essential to sustainable operation at industrial scale. The achieved process intensification in the new system has been analysed vis-a-vis the existing conventional systems in terms of eco-friendliness, flexibility, cost of equipment and production, consumption of energy and material, profitability, E-factor, atom efficiency and business sustainability.